Pemberian Pupuk Kompos Daun Kering Dan Poc Nasa Terhadap Pertumbuhan Dan Hasil Tanaman Sawi Hijau (Brassica Juncea L.) - Adlian Adlian; Wiji Safitri; Yeni Yurike Osok (Journal of Innovation Research and Knowledge, 2026)
This study aimed to analyze the effects of dried leaf compost and NASA Liquid Organic Fertilizer (LOF), applied individually and in combination, on the growth and yield of mustard greens (Brassica juncea L.). The research was conducted over a three-month period, from October to December 2025, at the Experimental Farm of the Faculty of Engineering and Agriculture, Nani Bili Nusantara University, Sorong. The experiment employed a factorial Randomized Complete Block Design (RCBD) consisting of two factors. The first factor was dried leaf compost with four treatment levels: K0 = no compost (control), K1 = 2 kg plot⁻¹ (20 t ha⁻¹), K2 = 3 kg plot⁻¹ (30 t ha⁻¹), and K3 = 4 kg plot⁻¹ (40 t ha⁻¹). The second factor was NASA Liquid Organic Fertilizer (LOF), consisting of three treatment levels: P0 = no LOF (control), P1 = 2 mL L⁻¹ of water, and P2 = 4 mL L⁻¹ of water. The data were statistically analyzed using analysis of variance (ANOVA) with an F-test at the 5% significance level. When significant differences were detected, mean comparisons were performed using the appropriate post hoc test. The results showed that the individual application of dried leaf compost and NASA Liquid Organic Fertilizer significantly improved the growth and yield of mustard greens, as indicated by increases in plant height, number of leaves, and fresh weight. The optimum growth and yield were achieved with the appropriate fertilizer dosage. However, the interaction between dried leaf compost and NASA Liquid Organic Fertilizer had no significant effect on any of the observed growth and yield parameters.